Cardiac Contractility Modulation in Patients with Ischemic versus Non-ischemic Cardiomyopathy: Results from the MAINTAINED Observational Study. (1st November 2021) - Fastner, Christian; Yuecel, Goekhan; Rudic, Boris; Schmiel, Gereon; Toepel, Matthias; Burkhoff, Daniel; Liebe, Volker; Kruska, Mathieu; Hetjens, Svetlana; Borggrefe, Martin; Akin, Ibrahim; Kuschyk, Juergen
Abstract: Background: Cardiac contractility modulation (CCM) is an FDA-approved device-based therapy for patients with systolic heart failure and normal QRS width who are symptomatic despite optimal drug therapy. The purpose of this study was to compare the long-term therapeutic effects of CCM therapy in patients with ischemic (ICM) versus non-ischemic cardiomyopathy (NICM). Methods: Changes in NYHA class, KDIGO CKD stage, left ventricular ejection fraction (LVEF), tricuspid annular plane systolic excursion (TAPSE), and NT-proBNP levels were compared as functional parameters. Moreover, observed mortality rates at 1 and 3 years were compared to those predicted by the MAGGIC heart failure risk score, and observed mortality rates were compared between groups for the entire follow-up period. Results: One hundred and seventy-four consecutive patients with chronic heart failure and CCM device implantation between 2002 and 2019 were included in this retrospective analysis. LVEF was significantly higher in NICM patients after 3 years of CCM therapy (35 ± 9 vs. 30 ± 9%; p  = 0.0211), and after 5 years, also TAPSE of NICM patients was significantly higher (21 ± 5 vs. 18 ± 5%; p  = 0.0437). There were no differences in other effectiveness parameters. Over the entire follow-up period, 35% of all patients died ( p  = 0.81); only in ICM patients, mortality was lower than predicted at 3 years (35 vs. 43%, p  = 0.0395). Conclusions: Regarding improvement of biventricular systolic function, patients with NICM appear to benefit particularly from CCM therapy. Highlights: Under CCM therapy, patients with NICM have more pronounced improvement in LVEF and TAPSE than patients with ICM in the long term. Patients with more severely impaired LVEF of 20 to 25% also benefit from CCM therapy. Safety events related to the device are rare with this therapy.